Graphene-oxide-based saturable absorber for all-fiber Q-switching with a simple optical deposition technique - Ahmad, H; Muhammad, Farah Diana; Zulkifli, Mohd Zamani; Harun, Sulaiman Wadi (IEEE, 2012)
A Q-switched erbium-doped fiber laser (EDFL) incorporating a graphene-oxidebased saturable absorber (SA) is proposed and demonstrated. The SA is fabricated by first dissolving graphene oxide nanopowder in water and subsequently using the thermophoresis effect to deposit it onto the fiber ferrule. The SA is integrated into a ring cavity EDFL, which uses a 3-m-long MetroGain Type-12 erbium-doped fiber (EDF) as the gain medium. The EDFL has a continuous-wave (CW) lasing threshold at a pump power of 9 mW, with Q-switching behavior observed at pump powers 18 mW and above. At the maximum pump power of 100 mW, the Q-switched pulses generated by the EDFL have a repetition rate and pulsewidth of 61 kHz and 6.6 s, respectively, along with an average output power of about 3.7 mW. Additionally, at the maximum power, the energy per pulse and peak power of the generated pulses are 61.3 nJ and 9.3 mW, respectively